Discovery of novel triazolobenzazepinones as γ-secretase modulators with central Aβ42 lowering in rodents and rhesus monkeys. Issue 17 (1st September 2015) - Fischer, Christian; Zultanski, Susan L.; Zhou, Hua; Methot, Joey L.; Shah, Sanjiv; Hayashi, Ikuo; Hughes, Bethany L.; Moxham, Christopher M.; Bays, Nathan W.; Smotrov, Nadya; Hill, Armetta D.; Pan, Bo-Sheng; et al.
Graphical abstract